The Rectus Abdominis Perforator Turndown Flap for Preserving Rectus Continuity: A DIEP Alternative? - Warren M. Rozen, MBBS, BMedSc, MD, PhD, FRACS; Robert Phan, MBBS; Marc A. Seifman, MBBS, BMedSc; Lisa Ellis, MBBS; David J. Hunter-Smith, MBBS, MPH, FRACS, FACS (Plastic and Reconstructive Surgery, Global Open, 2022)
Background:. The deep inferior epigastric artery perforator (DIEP) flap for breast reconstruction has been popularized over the transverse rectus abdominis myocutaneous (TRAM) flap, as it spares rectus abdominis muscle and has low donor site morbidity. This progression to muscle preservation, however, has been associated with an increased difficulty in vascular dissection, perfusion-related complications, and lengthier surgical times. We pilot a technique that may achieve the benefits of the TRAM flap in terms of ease of dissection and vascularity, with the benefits of the DIEP flap in terms of maintaining rectus abdominis continuity. Methods:. A cohort of six consecutive patients underwent a free TRAM flap for reconstructive surgery. All patients underwent a segmental, periumbilical harvest of rectus abdominis muscle as part of flap design, and the segmental defect was reconstructed with an innervated rectus abdominis perforator turndown (RAPT) flap harvested supraumbilically. Postoperative assessment of rectus continuity was performed clinically, with muscle electromyography and ultrasound. Results:. In all six cases, there was successful TRAM flap transfer, with no flap-related complications. Rectus abdominis muscle reconstruction with the RAPT flap was achieved, with continuity and function of the rectus muscle confirmed. Conclusions:. We describe the innervated RAPT flap for reconstitution of rectus continuity after TRAM flap harvest. This technique may achieve the benefits of the TRAM flap in terms of ease of dissection and flap vascularity, and the benefits of the DIEP flap in terms of maintaining rectus abdominis continuity.